Avaliação do efeito de parâmetros na produção do éster galato de isoamila por esterificação em meio de solvente catalisada por lipases nas formas livres - Passari, Gustavo José (2022)
The objective of this work was the enzymatic production of an ester with antioxidant activity (isoamyl gallate) by esterification of gallic acid and isoamyl alcohol in solvent medium (terc-butanol). For such purpose, eight commercial lipases from different sources were used in their free forms (crude enzymatic extracts) as biocatalysts: Mucor javanicus (LMJ), Rhizopus niveus (LRN), Thermomyces lanuginosus (LTL), Rhizomucor miehei (LRM), Candida sp. (LCsp), Candida rugosa (LCR) e Pseudomonas fluorescens (LPF) and porcine pancreas (LPP). After selecting the lipase sources with the highest catalytic performance on the ester production, it was evaluated the influence of relevant parameters on the reaction such as temperature (35°C–60°C), biocatalyst concentration based on the catalytic activity in olive oil emulsion hydrolysis (250 U–2000 U), molar ratio acid:alcool (1:1–:2) and reaction time. In this study, esterification reactions have been performed em closed flasks containing 5 mL of reaction mixture at fixed gallic acid concentration (250 mM) and mechanical stirring (240 rpm). The progress of the reaction has been measured by determining the residual gallic acid in the reaction by titrimetric method. According to results, maximum acid conversion percentage around 55% after 105 min of reaction using LPF and 40% after 90 min of reaction catalyzed by LPP were achieved under such experimental conditions: stoichiometric molar ratio acid:alcohol (1:1 – 250 mM of each reactant), 40ºC for LPP and 55°C for LPF, 1000 U of hydrolytic activity (0.12 g of LPF and 0.19 g of LPP). These results reveal that the application of a low-cost lipase as LPP can be highly promising for producing a lipophilic ester with antioxidant properties, an important class of compounds used in the food and cosmetic formulations.